Learning thresholds for early career occupational therapists: A grounded theory of learning-to-practise. (July 2020) - Murray, Carolyn M; Edwards, Ian; Jones, Mark; Turpin, Merrill
Introduction: Early career occupational therapists experience considerable learning. This research sought to develop a theory of how they learn once practising. Method: The research employed a constructivist grounded theory methodology. Interviews were conducted with 20 participants who were either experienced ( n = 8), early career occupational therapists ( n = 10) or in supporting roles for early career occupational therapists ( n = 2). Participants were asked their views about what early career occupational therapists find troublesome and how they respond. Data were collected and analysed concurrently. Open, focused and theoretical coding were used to develop a theory. Findings: The theory of learning-to-practise occupational therapy included four learning thresholds: consolidating professional reasoning; navigating into the workplace; building competence and confidence; and developing a personal theory and practise style. There were 11 strategies identified that early career occupational therapists use to cross the learning thresholds. Early career occupational therapists' understanding and value of knowledge shifted, which culminated in them 'realising' their personal theory and practice style. They refined their values and beliefs and learned to be more deliberate and reflective in their thinking and actions. Conclusion: Early career occupational therapists were challenged, which promoted learning. This research extends understanding of the learning needs, thinking and actions taken by early career occupational therapists to cross learning thresholds and to develop their personal theory and practice style.